Understanding Antecedents to the Satisfaction of Using Learning Management System: an Empirical Study of Accounting Students - Selfira Salsabilla; Chivalrind Ghanevi Ayuntari (Universitas PGRI Madiun, 2020)
ABSTRACTThis research was aimed to identify the factors affecting the Accounting students' satisfaction of using Google Classroom as one of the Learning Management System (LMS). This research analyzed the effect of perceived enjoyment, perceived ease of use, and perceived usefulness on the students' satisfaction. The sample in this research was 108 Accounting students. The data were analyzed using PLS-SEM with SmartPLS 2.0. The research results showed that the level of satisfaction of the Google Classroom was affected positively and significantly by the perceived enjoyment, perceived ease of use, and perceived usefulness. Moreover, this research also discussed the impacts of the results both theoretically and practically.ABSTRAKPenelitian ini bertujuan untuk mengidentifikasi faktor-faktor yang mempengaruhi kepuasan mahasiswa akuntansi dalam menggunakan google classroom yang merupakan salah satu learning management system (LMS). Penelitian ini menganalisis pengaruh perceived enjoyment, perceived ease of use, perceived usefulness terhadap kepuasan. Penelitian ini menggunakan sampel 108 responden mahasiswa akuntansi. Data dianalisis menggunakan PLS-SEM dengan software SmartPLS 2.0. Hasil penelitian menunjukkan bahwa tingkat kepuasan terhadap google classroom dipengaruhi secara positif signifikan oleh perceived enjoyment, perceived ease of use, dan perceived usefulness. Penelitian ini juga mendiskusikan dampak hasil penelitian dalam ranah teoritis dan praktis.